The Role of Islamic Higher Education Institution in Developing Students' Character Value - Wati Oviana; Fakhrul Rijal (STAI Hubbulwathan Duri, 2021)
The development of character values for students is an obligation for every higher education institution to ensure that students' national education goals and competency achievements can be carried out correctly. This study aims to describe and obtain data about the role of Islamic Higher Education Institution (PTKIN) Aceh in fostering student character values. The method used in this research is descriptive. Data was collected using qualitative research methods with data collection techniques in interviews, documentation, observation, and FGD. Data analysis was performed using data reduction techniques, data presentation and data verification and conclusion drawing. The results showed that the role of PTKIN Aceh in fostering student character values was carried out through the formulation of a vision and mission, curriculum, programs, rules, facilities, and the implementation of lecture activities that were oriented towards student character. Character planting in lecture activities is still carried out in various ways by each course instructor.